9 Investigating the counter regulatory renin angiotensin system axis in the stroke prone spontaneously hypertensive rat in ischaemic stroke. (26th March 2018) - McFall, Aisling; Zentilin, Lorena; Giacca, Mauro; Nicklin, Stuart A; Work, Lorraine M
Abstract : Several studies have assessed the potential of targeting the renin angiotensin system (RAS) with therapeutics for ischaemic stroke. The counter regulatory RAS peptide, angiotensin-(1–9) has been shown to act via the angiotensin II type 2 receptor (AT2 R) to oppose detrimental effects of RAS dysregulation. We hypothesise that Ang-(1–9) may have a beneficial effect on stroke outcome in the spontaneously hypertensive stroke prone rat (SHRSP). Initial qPCR experiments have assessed temporal changes in RAS gene expression (angiotensin converting enzyme 2; ACE2, AT2 R; AGTR2, Mas receptor; Mas ) following 35 min transient middle cerebral artery occlusion (tMCAO) followed by varying reperfusion times: no reperfusion (n=4), 2 hour (n=4) and 24 hour (n=4), compared to sham surgery (n=7). In infarcted tissue, there was a significant 10- and 11-fold reduction in ACE2 and Mas expression respectively, 24 hour post tMCAO vs sham (RQ+RQmax : ACE2: sham 1.0+0.2; 24 hour post tMCAO 0.1+0.01, p<0.01, Mas: sham 1.0+0.2; 24 hour post tMCAO 0.09+0.03 p<0.01). However, in the same tissue, AGTR2 showed a 4-fold increase in expression after 35 min occlusion vs sham (RQ+RQmax : sham 1.0+0.3; 35 min MCAO 4.2+0.2, p<0.05). Additionally, in the subcortical remainder tissue, ACE2 and AGTR2 expression decreased by 2.5- and 5-fold respectively 24 hour post tMCAO (RQ+RQmax : ACE2: sham 1.0+0.1; 24 hour post tMCAO 0.4+0.1, p<0.05, AGTR2: sham 1.0+0.4 ; 24 hour post tMCAO 0.2+0.1 p<0.05). These results demonstrate altered counter regulatory RAS gene expression in the ipsilateral hemisphere in the 24 hours following tMCAO in SHRSP. Additional experiments have demonstrated successful transduction of a control reporter gene-expressing, adeno-associated virus serotype 9 (AAV9) expressing enhanced green fluorescent protein (eGFP) (AAV9-eGFP) in the SHRSP brain via stereotactic delivery after both 4 and 7 days. Future studies will assess the therapeutic potential of Ang-(1–9) in tMCAO induced experimental stroke in SHRSP by delivering Ang-(1–9) via stereotactic delivery of an AAV9 vector.